Attitudes Toward Animal Welfare Among Adolescents from Colombia, France, Germany, and India. (4th May 2021) - Randler, Christoph; Ballouard, Jean-Marie; Bonnet, Xavier; Chandrakar, Priti; Pati, Atanu Kumar; Medina-Jerez, William; Pande, Babita; Sahu, Subhashis
ABSTRACT: Concerns about animal welfare are becoming increasingly important. Recent research suggests that age and gender are associated with attitudes toward animal welfare in adolescents. In this study, we analyzed attitudes toward animal welfare in adolescents from five geographic regions: Colombia, France, Germany, and two regions in India (Raipur and Kalyani). Individuals responded to the Composite Respect for Animals Scale (CRAS-S). The CRAS-S score integrates 10 facets of attitudes toward animal welfare: the use of animals in research, for food, as pets, for recreation, for clothing, farm animal husbandry, and the conservation of animals, as well as emotional aspects such as feeling superior to animals or emotional affection. A total of 627 males and 506 females ( n  = 1, 133) participated in this study (France, 134; Colombia, 193; Germany, 377; Raipur, 210; Kalyani, 219). Females scored significantly higher than males (2.9% of variance explained). There was no consistent relationship with age. No relationship was found in Colombia, France, and Raipur, and a negative relationship in attitudes toward animal welfare was found in Germany and Kalyani.